Unveiling the anti-oxidative potential of fruits and vegetables waste in prolonging the shelf stability of vegetable oils - Muqaddas Zahid; Samran Khalid; Sumbal Raana; Sara Amin; Hamza Javaid; Rizwan Arshad; Ayesha Jahangeer; Saeed Ahmad; Syed Ali Hassan (Future Foods)
Abstracts: Edible oils play a vital role in human nutrition, serving as a crucial source of energy, essential fatty acids, and vitamins necessary for bodily functions. However, during handling, cooking, and storage these oils are susceptible to oxidation, resulting in the loss of nutritional value, the development of undesirable flavors, the production of harmful compounds, and a reduction in shelf life. To counteract oxidation and enhance oil stability, synthetic antioxidants have traditionally been employed. However, in recent times, consumer awareness has led to an increased preference for natural antioxidants because of the harmful effects of synthetic antioxidants on human health. This review provides a comprehensive overview of recent research focused on the oxidative stability of various edible vegetable oils through the incorporation of natural antioxidants derived from fruits and vegetable waste. These antioxidants obtained from waste through diverse techniques are blended with different vegetable oils in the form of free extracts, encapsulated extracts, nano-encapsulated extracts, and nano-emulsion oil extracts to assess their antioxidant efficacy. These antioxidant-rich waste extracts efficiently prevented oxidation by scavenging free radicals, chelating metal ions, and delaying the formation of peroxides, offering a safer and more effective alternative to synthetic counterparts. Beyond their antioxidative properties, these extracts contribute to the nutritional enhancement of oils, functioning as nutraceuticals. This approach not only offers a natural means to protect edible oils but also facilitates efficient waste valorization, mitigating potential environmental impacts and making it a sustainable and eco-friendly strategy.